Idiopathic thyroid storm mimicking SIRS in a patient with hypothyroidism- a diagnostic dilemma. Issue 6 (2nd November 2018) - Shah, Syed Raza; Millan, Terance; Alamzaib, Sardar Muhammad; Luu, Sue-Wei
ABSTRACT: Thyroid storm, defined as an endocrine emergency in 1926, remains a challenge for physicians in the 21 st century. The mortality rate of untreated thyroid storm is very high. Hence, if a thyroid storm is suspected, treatment should not be delayed. This disease can be fatal! We present the case of a 86-year-old female presenting with altered mental status. All the tests came out negative except for elevated free t4 (ft4) with a very low TSH level (ft4-7.87, TSH< 0.005). Patient was diagnosed with thyroid storm in the setting of subclinical hypothyroidism and improved significantly with treatment. Furthermore, it is essential to confirm the TSH level in a patient with subclinical hypothyroidism. By carefully finding the extent of the disease, one can easily distinguish between hypo-or hyper- thyroid disease. The clinical features of thyroid storm may be related to other co-morbidities which makes diagnosis a clinical challenge. Nonetheless, it is important to be aware of the possibility of development of a thyroid storm in patients with a history of subclinical hypothyroidism. In addition, patients, if diagnosed with a thyroid storm, should be treated immediately with appropriate medications since thyrotoxicosis is life threatening.